Spatial production allocation model (SPAM) 2005: Technical documentation - Wood-Sichra, Ulrike; Joglekar, Alison B.; You, Liangzhi (International Food Policy Research Institute, 2019)
By 2050, world population is estimated to reach 9.7 billion people (United Nations 2015). The increased food, fiber and fuel demand from this population will significantly affect land and resource use, climate change, the nature and prevalence of poverty, political agendas and technological development. Preemptively addressing the effects of this increased demand is aided by a clear and reliable understanding of the current spatial distribution of cropping systems in the world. The Spatial Production Allocation Model (SPAM) 2005 endeavors to disaggregate crop statistics identified at national and sub-national units for the year 2005 to 5 arc-minute grid cells while taking account of different farming practices. SPAM generates four major output variables: physical area, harvested area, production quantity and yield for each of 42 crops distinguished by four production systems (i.e., irrigated – high input, rainfed – high input, rainfed – low-input and rainfed – subsistence production). The allocation model uses a cross-entropy optimization approach informed by major inputs such as cropland surface, location of irrigated areas, crop suitability and potential yields, rural population densities, production systems characteristics and crop prices to disaggregate crop statistics. Our primary intent is to document the data sources used to compile the SPAM2005 estimates, to outline the major features of the model itself, as well as the adjustments and modifications undertaken to generate these plausible spatial estimates of crop area, production and yield.